DAKWAH SOEKARNO MELALUI PIDATO - Mukoyimah, Mukoyimah (Jurnal Ilmu Dakwah, 2017)
Soekarno is a figure known as you mansionalis who aggressively fight for independence with the actions podiaumnya. But from some religious side of the Da'wah da'wah is da’i. because the values of da'wa is amar ma'ruf nahi munkar has been implemented. So in this paper aims to explain Sokarno from the side of da'wah that he did through his speeches. This type of research is qualitative bibliography and using textual and historical approach, while the data used is sampling some of Soekarno's speech. The Result of research that has been done can be generated that Soekarno is da’i who has the thinking of this element of visible in the fruit of thought that is gotong-royong, nationalism, and marhaenism. Sukarno also often repeated his words in a speech that aims to emphasize the important thing to be conveyed. Not only that, Sukarno's da'wah is not only to build a good understanding but also to show threat to the people